Early Results of a Novel Hybrid Prosthesis for Treatment of Acute Aortic Dissection Type A With Distal Anastomosis Line Beyond Aortic Arch Zone Zero - Mehdiani, Arash; Sugimura, Yukiharu; Wollgarten, Louise; Immohr, Moritz Benjamin; Bauer, Sebastian; Schelzig, Hubert; Wagenhäuser, Markus Udo; Antoch, Gerald; Lichtenberg, Artur; Akhyari, Payam (Frontiers in Cardiovascular Medicine, 2022)
Introduction Acute aortic dissection type A (AADA) is associated with high perioperative morbidity and mortality. A novel non-covered hybrid prosthesis (AMDS Hybrid Prothesis, Cryolife/Jotec, Hechingen, Germany) can be easily implanted in order to stabilize the true lumen (TL), improve remodeling and preserve organ perfusion. Although developed for implantation in aortic zone 0, occasionally partial replacement of the aortic arch and further distal implantation of AMDS may appear favorable. Implantation of AMDS with anastomosis line beyond zone 0 has not been described yet. Materials and Methods Between 08/2019 and 12/2020 a total of n=97 patients were treated due to AADA at a single university hospital. Of those, n=28 received an AMDS hybrid prosthesis, of whom in eight patients, due to intraoperative finding the distal anastomosis line was placed distal to the brachiocephalic trunk. Three had AMDS Implantation in zone 1, 4 were treated by implantation of the prostheses in zone 2 and one patient had the implantation performed in zone three. Clinical outcome and development of proportional area of TL and false lumen (FL) at defined levels of the thoracic aorta were analyzed. Results None of surviving patients (87.5%) showed signs of clinical malperfusion (i.e. stroke, spinal cord injury, need of dialysis). Postoperative CT-scan showed an open TL in all patients. The proportion of TL with respect to total aortic diameter (TL+FL) was postoperatively significantly higher in zone III (p=0.016) and at the level of T11 (p=0.009). Mean area of TL+FL was comparable between pre and postoperative CT-scan (p=n.s.). One patient with preoperative resuscitation died of multiple organ failure on extracorporeal life support at postoperative day three. Conclusions Implantation of AMDS can be safely performed in patients with the need for partial replacement of the aortic arch beyond zone 0. The advantages of the AMDS can be combined with those of the total arch repair (remodeling of the arch and prevention of TL collapse) without the possible disadvantages (risk of spinal cord injury).